A GAMBARAN PERSONAL HYGIENE PENJAMAH MAKANAN DI KANTIN SMP NEGERI 4 KOTA BENGKULU TAHUN 2024 - Yuliantini, Emi; Amanda, Aprilia; Okfrianti, Yenni (Poltekkes Kemenkes Bengkulu, 2024)
Background: The school canteen provides food and drinks for students or school personnel. Many canteens do not meet the quality requirements for cleanliness, health and safety, which has an impact on children's nutrition and health. Objective: The research revealed a description of the personal hygiene of food handlers in the canteen of SMP Negeri 4 Bengkulu City. Methods: This research is descriptive research with a qualitative approach and observations at 10 canteen booths and 18 food handlers at SMP Negeri 4 Bengkulu City. Results: The health condition of food handlers was 16 (89%) respondents good and 2 (11%) respondents poor. The personal hygiene of food handlers was 17 (94%) respondents good and 1 (6%) respondent poor. The habit of washing hands was 16 (89%) ) good respondents and 2 (11%) poor respondents. The behavior of food handlers in handling food of all 18 (100%) respondents was good. The appearance of food handlers was good for 16 (89%) respondents and 2 (11%) respondents were poor.. Conclusion: Food handlers showed that most of them had not implemented health conditions, maintained personal hygiene, hand washing habits and the appearance of food handlers when handling food.